(untitled) (Research, Society and Development, 2020)
Food and Nutrition Education is a mechanism to promote health through the construction of good eating habits, the school has been considered important for the development of this strategy. Therefore, the present study aimed to review the Brazilian scientific production on EAN interventions, and to analyze the effects of interventions in food and nutrition education in the school environment in Brazil, between the period 2014 to 2020. The sample of this review consisted of if initially of 31 articles that addressed the descriptors, and after the exclusion criteria that were publications of thesis, dissertation, monograph and articles that did not adhere to the theme, 10 articles remained that were addressed in this article. The chosen studies were characterized in the results according to the author, year, title, objective, type of study and results. Therefore, nutritional education addressed at school proved to be effective as a way to motivate students to change their diet, aiming to promote healthier eating habits for disease control.